Efektivitas Pupuk Organik dan Interval Penyiraman terhadap Pertumbuhan dan Produksi Tomat - Riska Nur Fateha; Bait Ilhaminnur; Soemarno Soemarno; Niken Rani Wandansari (Agrotechnology Research Journal, 2020)
This research aimed to determine the effect of various organic fertilizer and watering intervals on plant growth and tomato yield, also soil nutrient content. The method used was factorial completely randomized design with a combination of organic fertilizer types (kaliandra compost, water hyacinth and Mexican sunflower compost, cow manure and straw compost, and vermicompost) and watering intervals (1, 3 and 7 days). Mycorrhizal dose used was 2 grams/plant, while organic fertilizer used was 160 g/plant. The results showed that the interaction between organic fertilizer and watering intervals did not affected significantly on tomato plant height, stem diameter, root length, initial flowering, fruit diameter, number of fruits and fresh fruit weight and soil nutrient content. Watering interval affected significantly to all parameters of the observation. Addition of organic fertilizer can increase soil C-organic content by 6.58% and P-available by 170.51% compared to controls. In general, the highest tomato production was obtained in the combination of treatments water hyacinth and Mexican sunflower compost and watering interval of 1 day, which was 231 g/plant or equivalent 7.22 tons/ha.